Physical recreational activities plan to increase aged people participation in grandfather's club programm In Viñales's Community - María Isabel Hernández-Rábago; Adelina Saldaña-Carmona; Zaidelys Dopico-Portales (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
The present work has the objective to stimulate the interest, to increase the participation in the physical recreational activities and elevate the selfesteem of an aged people group in the San Vicente community. Mathematical, theoretical, empiric and statistical methods were used to know the preferences these people have about the recreational physical activities, which verified that there are insufficiencies in the in these activities participation. An exploratory study was carried out to know the reasons of these people misattendance physical recreational activities. It was revealed that they mainly didn't attend the activities because they didn't suit to their likes and preferences. This work offers a plan of activities that function as an appropriate tool to achieve the aged people participation in the activities of grandfather's club programme. The activities plan was submitted to the specialists´critera, supporting the idea that aged people from San Vicente community will be encouraged to participate in the activities due to these activities fit perfectly to their age. These activities influence in the increase of life's quality and their reinsertion in the society. This work has a practical meaning, so that it finds a way out to increase the performance of the activities of grandfather's club in San Vicente's community.